The most adverse fire scenario research of steel frame structure fire-resistant design based on structural vulnerability analysis. (December 2021) - Wenwen, Chen; Jihong, Ye
Abstract: The complex responses of the building under fire condition lead to difficult realization of structural fire-resistance design. By identifying the weakness areas, the defined most adverse scenario of the structural fire-resistance design has practical significance. In this paper, the characteristics of fire load, steel at elevated temperature and failure modes of steel beam and column in fire test, were discussed to determine that the damage consequences of steel components under fire were equivalent to component fracture. Meanwhile, the calculation method of joint well-formedness after component failure was given to recognize the failure mode of steel frame structure under fire condition based on structural vulnerability theory (SVT). Then, the most adverse fire scenario of the steel frame structure fire-resistance design under the conditions of single component failure and component failure continuously were analysed. The calculation method of the most adverse fire scenario based on the structural SVT was proposed. According to the failure mode identified by the SVT, the most adverse fire scenario was that the component with the minimum damage pattern subjected to fire in the condition of a single component failure occurred. When the component failed continuously, the components induced the maximum damage pattern (the vulnerability index was the largest) were the key components and such components exposed to fire was the most adverse fire scenario. Finally, two calculation models-6-story 4-span planar steel frame and 3D CFS composite shear wall structures-were selected to verify the proposed calculation of the most adverse fire scenarios. It was concluded that the proposed calculation method could reduce the number of fire scenarios that need to be calculated for design and was suitable for application to performance-based fire resistance design.